Optimisation of the Fabrication of Sidewall-Implanted Trenches in a 3.3 kV SiC Semi-Superjunction Schottky Barrier Diode - Renz, Arne Benjamin; Melnyk, Kyrylo; Iosifidis, Nikolaos; Jefferies, Richard; Zignale, Marco; Fiorenza, Patrick; Maresca, Luca; Irace, Andrea; Roccaforte, Fabrizio; Lophitis, Neophytos; Gammon, Peter Michael; Antoniou, Marina (My University, 2025)
In this paper we demonstrate a fully optimized process flow for silicon carbide semi-Superjunction (semi-SJ) Schottky barrier diodes, achieving high performance with readily available foundry technology. Using SF_6 -based etching, we fabricated 7 μm deep trenches with smooth, well-angled sidewalls (80-85°) and optimized implantation of the trench bottom and sidewalls. Scanning capacitance and atomic force microscopy, combined with TCAD simulations, confirmed the successful sidewall doping implantation. The resulting structures are expected to exhibit an RDSON of 6.2 mΩ⋯ cm2 and a 4 kV breakdown voltage, outperforming planar diodes. These advancements enable seamless integration of semi-SJ technology into SiC power devices, paving the way for next-generation high-voltage applications.
Keywords: SiC SuperJunction; Schottky Diode; MOSFET; Silicon carbide; High-voltage techniques; Capacitance; Foundries; Semiconductor process modeling